Epidemiology of Mortality Related to Chagas' Disease in Brazil, 1999–2007 - Martins-Melo, Francisco Rogerlândio (Public Library of Science, 2012)
BACKGROUND: Chagas' disease is an important neglected public health problem in many Latin American countries, but population-based epidemiological data are scarce. Here we present a nationwide analysis on Chagas-associated mortality, and risk factors for death from this disease. METHODOLOGY/PRINCIPAL FINDINGS: We analyzed all death certificates of individuals who died between 1999 and 2007 in Brazil, based on the nationwide Mortality Information System (a total of 243 data sets with about 9 million entries). Chagas' disease was mentioned in 53,930 (0.6%) of death certificates, with 44,537 (82.6%) as an underlying cause and 9,387 (17.4%) as an associated cause of death. Acute Chagas' disease was responsible for 2.8% of deaths. The mean standardized mortality rate was 3.36/100.000 inhabitants/year. Nationwide standardized mortality rates reduced gradually, from 3.78 (1999) to 2.78 (2007) deaths/year per 100,000 inhabitants (−26.4%). Standardized mortality rates were highest in the Central-West region, ranging from 15.23 in 1999 to 9.46 in 2007 (−37.9%), with a significant negative linear trend (p = 0.001; R(2) = 82%). Proportional mortality considering multiple causes of death was 0.60%. The Central-West showed highest proportional mortality among regions (2.17%), with a significant linear negative trend, from 2.28% to 1.90% (−19.5%; p = 0.001; R(2) = 84%). There was a significant increase in the Northeast of 38.5% (p = 0.006; R(2) = 82%). Bivariable analysis on risk factors for death from Chagas' disease showed highest relative risks (RR) in older age groups (RR: 10.03; 95% CI: 9.40–10.70; p<0.001) and those residing in the Central-West region (RR: 15.01; 95% CI: 3.90–16.22; p<0.001). In logistic regression analysis, age ≥30 years (adjusted OR: 10.81; 95% CI: 10.03–10.65; p<0.001) and residence in one of the three high risk states Minas Gerais, Goiás or the Federal District (adjusted OR: 5.12; 95% CI: 5.03–5.22, p<0.001) maintained important independent risk factors for death by Chagas' disease. CONCLUSIONS/SIGNIFICANCE: This is the first nationwide population-based study on Chagas mortality in Brazil, considering multiple causes of death. Despite the decline of mortality associated with Chagas' disease in Brazil, the disease remains a serious public health problem with marked regional differences.